The Process Of Creation And Dissolution Of The Universe In Bhuwana Sangksepa's Text - Anak Agung Raka Asmariani (Jayapangus Press, 2022)
Bhuana Sangksepa's text is a Shivaistic text classed as a Tattwatext due to its explanation of Shiva's supreme position in the universe. The text of Bhuana Sangksepa was chosen because it discusses cosmology in terms of the process of cosmos formation and dissolution. The issue that will be examined in this study is the process of the universe's formation and dissolution as described in Bhuana Sangksepa's text. This study employs hermeneutic qualitative research and data collection using library research techniques. The major data source for this study is the text of Bhuana Sangksepa, and the data will be examined descriptively before being provided in descriptive form. According to Bhuna Sangksepa's text, God is the source of all that exists. The universe began in a state of emptiness (Sunya). According to Bhuana Sangksepa's text, the universe's creation and disintegration are cyclical. The Samkya explains evolutionary cosmology by stating that the universe's expansion and contraction are ordered by degrees. The cosmos is composed of two layers: the upper layer (Sapta Loka) and the lower layer (Sapta Petala). Sapta Dwipa, Sapta Parwata, Sapta Samudra, and Sapta Tirtha comprise the universe. The notion of Tri Hita Karana explains the Hindus' understanding of cosmology in the Bhuana Sangksepa's text.